Pembuatan Standard Operating Procedure (SOP) di Orazio Multiusaha Indonesia - Irfania, Novi; Tjahjawati, Sri Surjani (Applied Business and Administration Journal, 2022)
Orazio Multiusaha Indonesia is an MSME engaged in women's fashion with robes and headscarves. Orazio Multiusaha Indonesia's operational activities are carried out in three places, the marketing office located in Cicaheum, and warehouses located in Sumbersari and Soreang. This causes poorly monitored management and supervision, unclear information, and ineffective communication. These problems are caused because Orazio does not have written work procedures yet so that every activity is carried out only based on the memories of its employees. As a result, there are missed work steps and errors occur in the implementation of activities. The purpose of this research is to make SOP for stock control and product sales. The result of this research is the SOP of stock control and product selling. The stock control SOP consists of three SOPs, namely SOP for procurement of goods, SOP for receiving goods, and SOP for releasing goods. The product selling SOP consists of two SOPs, namely SOP for product selling by COD and SOP for product selling by transfer.